Subjectivity of Women’s Body on Tiktok - Ratna Kumalasari (Retorik: Jurnal Ilmu Humaniora, 2021)
Tiktok has become very popular among people from various backgrounds, but especially among women. Although they can use Tiktok for a variety of activities, many women use Tiktok to show off their dances. This study argues that Tiktok application provides a medium for women to articulate their interpretation of their body that is limited by dominant discourses (especially around beauty) yet simultaneously liberating from everyday constraints. Through Tiktok, women show off their understanding of women’s bodies freed from the gendered prescriptions. This freedom of interpretation can be understood as women’s becoming the subject of their bodies. This study attempts to argue that in women’s embodiment in Tiktok, where women’s body is in contact with technology, the body has transformed its meaning into the posthuman body, to the extent it frees itself from the limitations of the body as bound to physiological function and fixed meanings.